The data do not seem to support a benefit to BCAA supplementation during periods of caloric restriction. Issue 1 (11th May 2016) - Dieter, Brad P.; Schoenfeld, Brad Jon; Aragon, Alan A.
Abstract: J Int Soc Sports Nutr 13:1-015-0112-9, 2016 describe the efficacy of branched chain amino acid (BCAA) supplementation and resistance training for maintaining lean body mass during a calorie-restricted diet, and claim that this occurs with concurrent losses in fat mass. However, the reported results appear to be at odds with the data presented on changes in fat mass. This letter discusses the issues with the paper.